Strategy for Enhancing Customer Loyalty Through Strengthening E-Service Quality and Brand Image with Customer Satisfaction as an Intervening Variable in the Use of BNI M-Banking in Bogor City - Dina Octaviana; Ing Soewarto Hardhienata; Hari Muharam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research was conducted to determine the effect of e-service quality and brand image on customer loyalty through customer satisfaction. This study aims to analyze the factors that influence customer loyalty in the use of BNI mobile banking in Bogor City. This research method uses a quantitative approach with survey techniques. The population used in this study were customers who use BNI mobile banking in Bogor City. The sampling technique used was Non-Probability Sampling with a Purposive Sampling procedure and Accidental Sampling method. The number of samples used in this study was 218 respondents. The analysis techniques used were Descriptive Statistics, Structural Equation Modeling (SEM), and SITOREM Analysis. The results of this study indicate that e-service quality affects customer satisfaction, brand image affects customer satisfaction, e-service quality affects customer loyalty, brand image affects customer loyalty, customer satisfaction affects customer loyalty, e-service quality and brand image together affect customer satisfaction, e-service quality, brand image, and customer satisfaction together affect customer loyalty, e-service quality affects customer loyalty through customer satisfaction, and brand image affects customer loyalty through customer satisfaction.